Modified technique for esthetic crown lengthening in the natural dentition: case series - Lobo, Maristela; Monteiro, Mabelle F.; Rodrigues, Rachel Q.F.; Xambre, Pedro A.O.; Rondina, Adriana R.; Andere, Naira M.R.B. [UNESP]; Castro dos Santos, Nidia C. (My University, 2022)
Aim: The objective of the present case series was to propose a modified technique for esthetic crown lengthening surgery (EC S) and a new method for cat egorizing esthetic parameters in terms of the gingival tissue as well as to assess treatment outcomes after 6 months. Materials and methods: Patients seeking ECLS were enrolled according to inclusion and exclusion criteria that are decribed in the materials and methods cri teria. Digital photographs were obtained at baseline and at 6 months postsurgery. Soft tissue cone beam computed tomography (ST-CBCT) was performed at baseline, and the dimensions of the periodontal tissue were digitally measured. All patients were submitted to the modified EC S. Periodontal esthetic outcomes were evaluated according to the crown lengthening esthetic score (C ES) system. The mean C ES and its subdomains (gingival zenith [GZ], papillae, and gingi val recession [GR]) were compared at baseline and 6 months using the paired t test and the Wilcoxon signed-rank test. Results: Fifteen patients were assessed. At 6 months, the mean C ES (15.23 ± 2.49 to 20.30 ± 2.65), GZ (4.80 ± 1.17 to 7.28 ± 1.97), and papillae (4.62 ± 2.30 to 7.30 ± 0.95) presented statistically significant dif ferences compared with baseline. GR did not present significant changes at 6 months. Conclusions: The modified EC S technique effective ly improved esthetic periodontal parameters in the present case series. The C ES system may be a useful tool for assessing EC S outcomes.